GAMMA RADIATION EFFECTS ON THE PERFORMANCE OF MONO-CRYSTALLINE SOLAR CELLS - Soni Prayogi; Zainuddin Zainuddin (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2023)
In this study, we present examples of solar cells that were subjected to various levels of 60Co gamma radiation. The solar cells we use are mono-crystalline, which has a stable crystal structure and high efficiency compared to polycrystalline. Prior to and during gamma irradiation, the current-voltage characteristics of monocrystalline silicon solar cells under AM1.5 light conditions and their photon spectral currents were examined. The results of the experiment demonstrate that as the dose of gamma radiation increases, solar cell metrics including open circuit voltage (Voc), short circuit current (Isc), and efficiency (Î·) drop. The photon spectral current demonstrates that as dose gamma is increased, the current decreases at shorter wavelengths Â and the defects are primarily produced near the solar cell's surface. Our findings demonstrate the gamma irradiation-induced breakdown of silicon solar cells and the minority carrier lifetime which demonstrates that the minority carrier lifetimes sharply decline with increasing radiation dose.